Effects of paternal ionizing radiation exposure on fertility and offspring's health - Jiaqun Li; Juan Liu; Yanye Zhang; Hong Qiu; Junyan Zheng; Jinglei Xue; Jiani Jin; Feida Ni; Chunxi Zhang; Chuan Chen; Xiao Sun; Huiquan Wang; et al. (Reproductive Medicine and Biology)
Abstract Purpose The intergenerational effects of ionizing radiation remain controversial. Extensive insights have been revealed for DNA mutations and cancer incidence in progeny, yet many of these results were obtained by immediate post‐radiation mating. However, conception at short times after radiation exposure is likely to be avoided. After a long period of fertility recovery, whether unexposed sperm derived from exposed spermatogonia would challenge the health of the offspring is not yet clearly demonstrated. Methods Ten‐week‐old C57BL/6J males underwent whole‐body acute γ irradiation at 0 and 6.4 Gy. Testes and sperm were collected at different times after radiation to examine reproductive changes. The reproductive, metabolic, and neurodevelopmental parameters were measured in the offspring of controls and the offspring derived from irradiated undifferentiated spermatogonia. Results Paternal fertility was lost after acute 6.4 Gy γ radiation and recovered at 10–11 weeks post irradiation in mice. The reproductive, metabolic, and neurodevelopmental health of offspring born to irradiated undifferentiated spermatogonia were comparable to those of controls. Conclusion The male mice could have healthy offspring after recovery from the damage caused by ionizing radiation.